SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN DESTINASI WISATA FAVORIT DI PROPINSI YOGYAKARTA DENGAN METODE WEIGHTED PRODUCT (WP) BERBASIS ANDROID - Anton Setiawan Honggowibowo; Asih Pujiastuti; Suryanto Suryanto (Institut Teknologi Dirgantara Adisutjipto, 2017)
Yogyakarta is a province that has many excellent tourist destination. In this research will be discussed about choosing an accurate tourist spot for tourists by using decision-making system with weighted product method, in this thesis the writer take 3 criterion as supporting of SPK calculation that is cost, mileage and tourist visit. SPK application created has various features such as the calculation of the ranking value of each resort, location information and other supporting information. In this study produce an android application that serves as a supporter in decision making a tourist who will travel. Based on testing done this SPK application displays an accurate calculation with a calculation difference of 0.00587 of manual calculations. Applications that are made to run minimal on android version 4.0.3 is ice cream sandwich or above. The average value generated from the tests and trials with the questionnaire yielded a value of 70.95% scale, so the tests and trials based on the questionnaires were included in very good category.